Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/cmar.s252801
|View full text |Cite
|
Sign up to set email alerts
|

<p>Breast Cancer Brain Metastasis: The Potential Role of MRI Beyond Current Clinical Applications</p>

Abstract: Breast cancer brain metastasis (BCBM) represents a major clinical challenge. Can MRI help in advancements in the management of BCBM? This review discusses MRI developments and the corresponding potential advancements in BCBM management. Methods: An exhaustive literature search was undertaken to identify studies which look into the potential of MRI in BCBM management. Seven hundred and eighty-four studies published from September 1984 to May 2020 were identified. Three topics are covered where MRI is not clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
(80 reference statements)
1
13
0
1
Order By: Relevance
“…Patients with HER2-positive characteristics had a longer life expectancy than patients with HER2-negative disease (18 versus 11 months; p=0.02). [11] This observation is consistent with a recent study examining the effect of HER2 expression on patient outcomes after diagnosis of brain metastases. In a cohort of 60 patients treated with stereotactic radiosurgery, another study demonstrated an extended 1-year survival rate in HER2-positive patients treated with trastuzumab compared with similar patients with HER2-negative disease (78% vs 55%; p=0.02).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with HER2-positive characteristics had a longer life expectancy than patients with HER2-negative disease (18 versus 11 months; p=0.02). [11] This observation is consistent with a recent study examining the effect of HER2 expression on patient outcomes after diagnosis of brain metastases. In a cohort of 60 patients treated with stereotactic radiosurgery, another study demonstrated an extended 1-year survival rate in HER2-positive patients treated with trastuzumab compared with similar patients with HER2-negative disease (78% vs 55%; p=0.02).…”
Section: Discussionsupporting
confidence: 92%
“…Lapatinib is a tyrosine kinase inhibitor directed against epidermal growth factor receptor (EGFR) and HER2. This compound has a much lower molecular weight than trastuzumab (943 Da) compared to 148,000 Da) and it has been reported by various studies that it can cross the blood-brain barrier [11], [13]. A phase II study, reported that 66% of patients with brain metastases previously untreated HER2-positive metastatic breast cancer responded well to combination therapy with lapatinib plus capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional patient samples and molecular studies on in vitro BBB models should be conducted in further investigations. A major problem is the recruitment of patients with brain metastases, as clinically normal patients are not routinely screened for brain metastases [ 50 ], while the incidence at autopsy is much higher [ 51 ]. There are rarely patients with only brain metastases, as most of them demonstrate visceral metastases first and, in the further course of the disease, the formation of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…This might result from the timing of brain imaging after patients have symptoms. Currently, controversies exist on the role of brain magnetic resonance imaging (MRI) as a screening tool for BM [ 21 ]. However, recent studies emphasize and favor the use of MRI because early detection of BM could be managed by SRS with less invasiveness and toxicities [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%